Hacia un estudio del cuerpo y la grupalidad en la formación actoral del teatro independiente de la ciudad de Córdoba (Argentina) - Yurquina, Paulette (2023)
This paper will pose some initial questions for the development of my doctoral research process. Starting from the premise that acting in the city of Córdoba (Argentina) is configured in spaces of acting training, through the proposed link between an ethics of being with others and the construction of corporeality. Therefore, this research aims to study the acting training of some independent theater groups in the city of Cordoba, specifically the ideas of acting that underlie these trainings, what skills are sought to develop, what corporealities are built through acting training and how the group dimension operates in the training processes. My interest lies in achieving a characterization of acting training in the independent theater of the city of Córdoba with the purpose of contributing to a situated conception of acting. Thus, in the present paper, I will propose the unfolding of the research problematic and some uncertainties and methodological challenges to address the following questions: Why focus on the body and groupality? In a city where formal and non-formal spaces of acting training coexist, how to delimit a corpus of analysis that can account for this particularity and at the same time specify representative acting poetics of the field? What are the most appropriate procedures to recover or reconstruct experiences of teaching and learning processes? How to generate crossings between different disciplinary fields to address the research problem?